1997
DOI: 10.1172/jci119287
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-enriched foods and bone mass growth in prepubertal girls: a randomized, double-blind, placebo-controlled trial.

Abstract: High calcium intake during childhood has been suggested to increase bone mass accrual, potentially resulting in a greater peak bone mass. Whether the effects of calcium supplementation on bone mass accrual vary from one skeletal region to another, and to what extent the level of spontaneous calcium intake may affect the magnitude of the response has, however, not yet been clearly established. In a doubleblind, placebo-controlled study, 149 healthy prepubertal girls aged 7.9 Ϯ 0.1 yr (mean Ϯ SEM) were either al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
339
7
19

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 512 publications
(381 citation statements)
references
References 43 publications
12
339
7
19
Order By: Relevance
“…There is evidence that increased intake of dairy foods and calcium may play a significant role in maintaining a healthful weight and moderating body fat (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, results across studies have been inconsistent (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), and this may be attributable to major challenges in using self-reported dietary intake data. Self-reported intakes tend to be subject to underreporting bias and the underreporting of energy intake tends to be positively related to weight status.…”
mentioning
confidence: 99%
“…There is evidence that increased intake of dairy foods and calcium may play a significant role in maintaining a healthful weight and moderating body fat (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). However, results across studies have been inconsistent (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), and this may be attributable to major challenges in using self-reported dietary intake data. Self-reported intakes tend to be subject to underreporting bias and the underreporting of energy intake tends to be positively related to weight status.…”
mentioning
confidence: 99%
“…9 -12 Although it is expected that children of different genders and socioeconomic background would have different lifestyles (exercise, sunlight exposure, and nutrition), the few studies evaluating vitamin D levels in children and adolescents have mostly done so in boys and have not systematically examined the impact of socioeconomic status (SES) on vitamin D levels. An increasing body of evidence confirms a key role of calcium in bone mass accretion in children and adolescents [13][14][15] ; however, the impact of vitamin D insufficiency and, therefore, repletion on skeletal integrity in this age group is yet to be determined. …”
mentioning
confidence: 99%
“…Even after adjusting for height, calcium intake, vitamin D status and TBLH BA, the gain in TBLH BMC remained significantly greater in the group who were administered calcium fortified laddoos. Calcium supplementation resulted in significantly higher serum concentrations of iCa and a decrease in the serum concentrations of intact parathyroid hormone in the study group than the control group toddlers who received only vitamin D. Toddlers from the study group showed a significant increase in TBLH BMC of 35% as against 28% in the control group, which is higher than the increase observed in other calcium supplementation studies (Johnston et al, 1992;Lee et al, 1994a, b;Bonjour et al, 1997;Cadogan et al, 1997;Specker et al, 2001;Specker and Binkley, 2003;Lambert et al, 2008). Calcium supplementation with pharmacologic preparations in children has been studied by various researchers, although studies in toddlers and preschool children are scant.…”
Section: Discussionmentioning
confidence: 61%
“…Calcium fortification of fruit juice was used by Lambert et al (2008) in 12-yearold girls and a significantly greater increase in TBLH BMC was observed in the supplemented group than the placebo. Fortification of several foods with milk extracts has shown to bring about greater increase in BMD in prepubertal girls with low calcium intakes (Bonjour et al, 1997).…”
Section: Discussionmentioning
confidence: 99%